The Power of Design: Product Innovation in Sustainable Energy Technologies. Edited by Angèle Reinders, Jan Carel Diehl, and Han Brezet. Issue 7 (17th July 2013) - Psomopoulos, Constantinos S.
<x xml:space="preserve">Abstract</x> Wiley, Chichester 2012, 331 pp., €73.90—ISBN 978‐1‐118‐30867‐7<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>